2021
DOI: 10.1007/s10792-021-01763-8
|View full text |Cite
|
Sign up to set email alerts
|

New pharmacotherapy options for noninfectious posterior uveitis

Abstract: Introduction Noninfectious inflammation of the posterior eye segment represents an important cause of visual impairment. It often affects relatively young people and causes a significant personal and social impact. Although steroids and nonbiologic- Disease-Modifying Antirheumatic Drugs (nbDMARDs) are effective both in acute and long- lasting diseases, however they are increasingly being replaced by biologic (DMARDs). bDMARD. This article therefore aims to identify recent advances i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 104 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…In these patients, topical steroids are the major treatment for acute anterior uveitis. Nevertheless, uveitis with posterior or bilateral involvement, or refractory to topical medication, required systemic treatment such as systemic steroids, DMARDs, or biologic agents (45,48). Under these conditions, systemic steroids were the first choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, topical steroids are the major treatment for acute anterior uveitis. Nevertheless, uveitis with posterior or bilateral involvement, or refractory to topical medication, required systemic treatment such as systemic steroids, DMARDs, or biologic agents (45,48). Under these conditions, systemic steroids were the first choice of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosteroids remain to be the mainstay treatments for APU, they may cause signi cant side effects to pediatric patients. Currently, there is no reliable indicator to guide treatment duration [35], and patients are at risk of being treated inadequately or excessively. In our study, multiple linear regression revealed that FAZ, CMT, and DCP VD were factors strongly correlated with CFD.…”
Section: Discussionmentioning
confidence: 99%
“…Robust, conventional immune responses, for instance in the lung, the gut or the skin, have a good chance of clearing the infection and restoring tissue homeostasis in an otherwise healthy individual. In contrast, the attenuated immunity of IP does not seem to be very effective either in clearing the infection or preventing intraocular inflammation (IOI) [uveitis is a significant cause of blindness, www.who.int/blindness (28)]. Moreover, IP has not been demonstrated convincingly for infectious foreign antigens [reviewed in (5)].…”
Section: Immune Privilege Is One Form Of Immunological Tolerancementioning
confidence: 99%